Effectiveness of Localization and Brand Equity: The Case of Agoda in the Indonesian Domestic Travel Market - Ida Bagus Putu Kawibhawa Suputra; I Made Darma Oka; Made Satria Pramanda Putra; Made Ernawati; Ni Made Sudarmini (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This study aims to assess how Agoda's localization strategies enhance brand equity among Indonesian domestic travelers, identifying which localization elements (linguistic, cultural, and technical) most effectively strengthen consumer perception and brand engagement. Research Methods: A mixed-method approach was used combining quantitative analysis from 177 questionnaire respondents with qualitative insights from interviews and FGDs. Findings: Cultural localization had the strongest impact on brand equity, followed by linguistic localization, and technical localization. Respondents perceived localized features as more trustworthy, relevant, and easier to use. Brand equity outcomes such as brand recall, recognition, and association were significantly influenced by these elements. Implication: Multinational OTAs must go beyond translation to achieve brand relevance through cultural sensitivity, linguistic familiarity, and local technology integration.